Safety assessment of the process Bangladesh Petrochemical Company, based on the Vacurema Prime technology, used to recycle post‐consumer PET into food contact materials. (23rd June 2022) - ,; Lambré, Claude; Barat Baviera, José Manuel; Bolognesi, Claudia; Chesson, Andrew; Cocconcelli, Pier Sandro; Crebelli, Riccardo; Gott, David Michael; Grob, Konrad; Mengelers, Marcel; Mortensen, Alicja; Rivière, Gilles; et al.
Abstract: The EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP Panel) assessed the safety of the recycling process Bangladesh Petrochemical Company (EU register number RECYC246), which uses the Vacurema Prime technology. The input material is hot caustic washed and dried poly(ethylene terephthalate) (PET) flakes originating from collected post‐consumer PET containers, including no more than 5% PET from non‐food applications. The flakes are heated in a batch reactor (step 2) ■■■■■ and then heated in a continuous reactor (step 3) ■■■■■ before being extruded into pellets. Having examined the challenge test provided, the Panel concluded that step 2 and step 3 are critical in determining the decontamination efficiency of the process. The operating parameters to control the performance of these steps are temperature, pressure and residence time. The Panel concluded that this recycling process is able to ensure that the level of migration of potential unknown contaminants into food is below the conservatively modelled migration of 0.1 μg/kg food. Therefore, the recycled PET obtained from this process is not of safety concern, when used at up to 100% for the manufacture of materials and articles for contact with all types of foodstuffs for long‐term storage at room temperature, with or without hotfill. The final articles made of this recycled PET are not intended to be used in microwave and conventional ovens and such uses are not covered by this evaluation.